Zasady przeliczania nakładów finansowych poniesionych w latach 1945–2010 przez Muzeum Pałacu w Wilanowie i jego poprzednika prawnego - Kłusek, Mirosław (Annales. Etyka w Życiu Gospodarczym, 2014)
Between 1945 and 2010 the Palace Museum in Wilanów and its legal predecessor incurred particular financial costs which could be expressed in money (in circula-tion), in nominal values. The aim of this article is to express the costs according to unchanged price measures: the American dollar, gold and rye.The conducted research shows that the overall costs borne by The Palace Museum in Wilanów between 1945 and 2010 were 297 mln zł (Polish currency), after counting which included money exchange and denomination, or $124 mln (in USD). According to the average exchange rate in 2010, it gives the sum of 375 mln zł ($1 equals 3,02 zł). The costs measured in rye equalled 10.5 mln q (average price of rye in 2010 was 1 q = 42,12 zł). In the end, it gives the sum of 442 mln zł. As to world gold prices, the costs were 542,000 ounces of pure gold (in 2010 1 ounce of gold costs $1421,6). It gives $771 mln according to the average exchange rate in 2010 and 2329 mln zł ($1 = 3,02 zł).It can be a matter of discussion which one of these three measures shows the real value of the costs incurred since 1945. Fortunately, there is no question that a counting method which takes into consideration exchanged money and denomination ought not to be used in measuring nominal values.